Pressing the buy button: generation Y's online clothing shopping orientation and its impact on purchase - Loureiro, S. M. C. (2017)
The authors investigated the effect of the nine most accepted factors of online shopping orientation on online purchase intention through perceived behavioral control and attitude toward purchase of clothing. They suggest that in-home shopping tendency, convenience consciousness, and impulse purchase are the most significant constructs in building consumers’ online shopping orientation. Impulse and convenience for online shoppers appear to be more important than recreational shopping. Online shopping orientation seems to have a positive influence on perceived behavioral control and attitude toward purchase. Implications of the results are discussed to provide guidance for managers and future researchers.